Problem-Based Learning as an Innovative Approach in Elementary Social Studies Education: A Thematic Analysis of Empirical Studies - Burhan, Imron (Journal of Education Method and Learning Strategy, 2026)
Social Studies learning in elementary schools is required not only to focus on the mastery of concepts but also to promote the development of critical thinking skills, problem-solving abilities, and active student participation. One instructional approach considered capable of addressing these demands is Problem-Based Learning (PBL). This study aims to thematically analyze empirical research findings on the implementation of PBL in elementary Social Studies education. The research method employed is a literature review using a qualitative approach based on thematic analysis of national scholarly articles published between 2018 and 2025. The data were analyzed through coding procedures and the categorization of research findings into major themes. The results indicate that the implementation of PBL consistently improves students’ Social Studies learning outcomes, enhances critical thinking and higher-order thinking skills, and increases students’ motivation, activeness, and engagement in learning. Furthermore, the integration of PBL with various instructional media has been shown to strengthen the effectiveness of Social Studies learning, although challenges related to teacher readiness and limited supporting facilities remain. This study concludes that PBL is an innovative, effective, and relevant instructional approach for improving the quality of Social Studies education in elementary schools and has important implications for the development of instructional practices and future research.